ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KINERJA APARAT PENGAWAS INTERNAL PEMERINTAH DENGAN STRES KERJASEBAGAI VARIABEL MODERATING PADA INSPEKTORAT KABUPATEN HUMBANG HASUNDUTAN - Naibaho, Pani Romauli Elisabet; Maksum, Azhar (Jurnal Riset Akuntansi & Keuangan, 2024)
This research aims to analyzing factors affecting performance of the APIP (Government Internal Supervisory Apparatus) at the Humbang Hasundutan Regency, using workplace stress as a moderating variable. The causal research which aims to identify the influence of independent variables on the dependent variable by analyzing and processing data in the form of numbers. The sample in this research was the Government Internal Supervisory Apparatus (APIP) of Humbang Hasundutan Regency, numbering 54 people. The results in this study show that the competency (Variable X1) has a positive and significant effect on the APIP performance (Variable Y). The results in this study show that the motivation variable as educational background as X3 has a positive and significant effect on the APIP performance variable Y. The results in this study show that the independence variable as between competency (Variables X1), motivation (variable X2), educational background (Variable X3), independence (variable X4), with APIP performance (Variable Z) at the Inspectorate of Humbang Hasundutan Regency.